IMPLEMENTASI NILAI-NILAI BUDAYA HUKUM DALAM KEHIDUPAN MASYARAKAT - Rila Kusumaningsih; Dwi Yulianingsih; Irma Welly (LP4MK STKIP PGRI Lubuklinggau, 2023)
This journal aims to measure theoretically the correlation of society, law, and culture in the dimensions of theory and practice. In the dimension of legal practice, it is closely related to culture. Law itself is a product of culture, because actually a legal product is a product of human creation. Law can be used as a means of change and renewal of society. In addition, law is positioned as a means of driving development, or then law can function as a means of dispute settlement. In general, this study uses normative juridical research methods. The approach in this method is used as an effort to deepen all aspects of law formation, the relationship between law and culture, to its implementation in social life. The results of this study indicate that society, culture and law are three interrelated components. Law is a product of culture and has a role in regulating people's behavior and shaping attitudes and behavior internalized by society. The relationship between culture and law is mutually influencing and plays an important role in the formation of norms, values, behavior, and collective identity in society